Factors associated with oxidative stress in virologically suppressed people living with HIV on long-term antiretroviral therapy - Francesca Lombardi; Simone Belmonti; Alessia Sanfilippo; Alberto Borghetti; Valentina Iannone; Pierluigi Francesco Salvo; Massimiliano Fabbiani; Elena Visconti; Simona Di Giambenedetto (AIDS Research and Therapy)
Abstract Background Oxidative stress (OS) is the imbalance between oxidant and antioxidant molecules, in favour of oxidants, that has been associated with an increased risk of morbidity and mortality in ART-treated people living with HIV (PLWH). We aimed to assess factors associated with OS in virologically suppressed PLWH on long-term modern ART. Method In this cross-sectional study we evaluated OS by measuring both the levels of derivatives-reactive oxygen metabolites (d-ROMs) and the biological antioxidant potential (BAP). We also calculated the BAP/d-ROMs ratio, (OS index, OSi); a cut-off value < 7.3 indicated OS. Factors associated with OS markers were explored by linear regression model. Results We enrolled 299 experienced PLWH with virological suppression (HIV-RNA < 50cps/mL). The mean of the d-ROMs levels was 409 UCARR (95%CI 394–422), whereas the mean of the BAP levels was 1.809 µmol/L (95%CI 1706–1851). The OSi mean value was 4.84, and 91.6% of the participants were below the cut-off value. By regression analysis, higher production of oxidants was associated with female sex (p < 0.001), current exposition to PIs (p = 0.030) and HCV co-infection (p = 0.006). Higher antioxidant capacity was correlated with higher HDL levels (p = 0.001). A lower OSi was associated with female sex (p = 0.003) and the current use of triple vs. dual regimen (p = 0.036). The OSi correlated negatively with cholesterol levels (p = 0.002) and positively with HDL (p < 0.001). Conclusions Virologically suppressed PLWH on long-term ART showed a marked OS. Female sex, the exposure to PIs, and HCV co-infection were associated with higher oxidants, while higher HDL levels were linked to better antioxidant capacity. Interestingly, dual therapy, especially INSTI-based regimens, was associated with lower oxidative stress compared to triple therapy.